Array comparative genomic hybridization reveals similarities between nodular lymphocyte predominant Hodgkin lymphoma and T cell/histiocyte rich large B cell lymphoma. (2nd February 2015) - Hartmann, Sylvia; Döring, Claudia; Vucic, Emily; Chan, Fong Chun; Ennishi, Daisuke; Tousseyn, Thomas; de Wolf‐Peeters, Christiane; Perner, Sven; Wlodarska, Iwona; Steidl, Christian; Gascoyne, Randy D.; Hansmann, Martin‐Leo
Summary Nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) and T cell/histiocyte rich large B cell lymphoma (THRLBCL) usually affect middle‐aged men, show tumour cells with a B cell phenotype and a low tumour cell content. Whereas the clinical behaviour of NLPHL is indolent, THRLBCL presents with advanced stage disease and an aggressive behaviour. In the present study, array comparative genomic hybridization was performed in seven typical NLPHL, four THRLBCL‐like NLPHL variants, six THRLBCL and four diffuse large B cell lymphomas (DLBCL) derived from NLPHL. The number of genomic aberrations was higher in THRLBCL compared with typical and THRLBCL‐like variant of NLPHL. Gains of 2p16.1 and losses of 2p11.2 and 9p11.2 were commonly observed in typical and THRLBCL‐like variants of NLPHL as well as THRLBCL. Gains of 2p16.1, affecting the REL locus were confirmed in an independent cohort. Expression of the REL protein was observed at similar frequencies in typical and THRLBCL‐like variant of NLPHL as well as THRLBCL (33–38%). In conclusion, the present study reveals further similarities between NLPHL and THRLBCL on the genomic level, confirming that these entities are part of a pathobiological spectrum with common molecular features, but varying clinical presentations.